2022
DOI: 10.1017/s0954579421001760
|View full text |Cite
|
Sign up to set email alerts
|

Preconception maternal posttraumatic stress and child negative affectivity: Prospectively evaluating the intergenerational impact of trauma

Abstract: The developmental origins of psychopathology begin before birth and perhaps even prior to conception. Understanding the intergenerational transmission of psychopathological risk is critical to identify sensitive windows for prevention and early intervention. Prior research demonstrates that maternal trauma history, typically assessed retrospectively, has adverse consequences for child socioemotional development. However, very few prospective studies of preconception trauma exist, and the role of preconception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 97 publications
2
16
0
Order By: Relevance
“…For example, children of parents with PTSD are at higher risk of PTSD (Leen-Feldner et al, 2013;Scheeringa & Zeanah, 2001;. Concurrent work in this cohort reports that prepregnancy maternal PTSD symptoms are associated with greater child negative affectivity in early childhood (Swales et al, 2022) factors may also contribute. For example, the transition to kindergarten typically occurs around the age of 5 years and may lead to changes in daily routine that affect wake time, morning routine, levels of stress, and diurnal cortisol patterns in children (Bruce et al, 2002;Quas et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…For example, children of parents with PTSD are at higher risk of PTSD (Leen-Feldner et al, 2013;Scheeringa & Zeanah, 2001;. Concurrent work in this cohort reports that prepregnancy maternal PTSD symptoms are associated with greater child negative affectivity in early childhood (Swales et al, 2022) factors may also contribute. For example, the transition to kindergarten typically occurs around the age of 5 years and may lead to changes in daily routine that affect wake time, morning routine, levels of stress, and diurnal cortisol patterns in children (Bruce et al, 2002;Quas et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…For example, children of parents with PTSD are at higher risk of PTSD (Leen‐Feldner et al., 2013; Scheeringa & Zeanah, 2001; Yehuda & Bierer, 2007). Concurrent work in this cohort reports that prepregnancy maternal PTSD symptoms are associated with greater child negative affectivity in early childhood (Swales et al., 2022). Blunted diurnal cortisol may be indicative of psychological differences in mental health risk or may serve as a mechanism underlying the intergenerational effects of traumatic experiences.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Stressors encountered by women prior to becoming pregnant can affect offspring birth weight [ 103 ], fetal brain development, and postnatal psychological disorders [ 104 ], which could potentially come about due to the distress related to persistent negative rumination. A prospective analysis similarly revealed that preconception PTSD was associated with elevated negativity when children were 3–5 years old, even after controlling for prenatal and postnatal depressive symptoms or sociodemographic factors [ 105 ].…”
Section: Neurobiological Consequences Of Early-life Traumamentioning
confidence: 99%